Hermeneutika al-Qur’an Nasr Hamid Abu Zaid: Suatu Pembacaan Hermeneutis Kritis - M. Abd. Rouf, M. Abd. Rouf (Universitas Nahdlatul Ulama Blitar, 2023)
As a way of life, religion—recitation on it through primary texts: the Qur'an and hadith—is always interesting to learn. Moreover, they are not only seen as a source of the truth but also as the axis of all religious activities. Therefore, define, read, and interpret them according to the needs of the times is an inevitability. Of course, recitation on it must be accompanied by scientific awareness of tradition in order to produce a current contextual understanding. This paper aims to examine the hermeneutics of al-Qur'an, based on Nasr Hamid Abu Zaid’s thought in masterpieces . Based on the comparative thought's method and critical analysis, concluded that learning religion—and the texts on it—requires an inclusive perspective, 1). Differentiation between religion and religious thought based on scientific awareness of tradition, 2). Viewing the Qur'an as a text in which various cultural variables are involved in its formation; 3). There are three semantis levels in producing meaning; historical meaning, metaphorical meaning, and semantic inner meaning.